Fifteen-year survival of resin-bonded vs full-coverage fixed dental prostheses. Issue 3 (July 2019) - Yoshida, T.; Kurosaki, Y.; Mine, A.; Kimura-Ono, A.; Mino, T.; Osaka, S.; Nakagawa, S.; Maekawa, K.; Kuboki, T.; Yatani, H.; Yamashita, A.
Abstract: Purpose: We clarified cumulative survival and event-free rates of resin-bonded fixed dental prostheses (RBFDPs) and compared them to those of fixed dental prostheses (FDPs) to refine risk factors for non-survival/event and use of tooth extraction after the period of non-survival/event. Methods: Study subjects were selected among all patients who consecutively attended the Fixed Prosthodontic Clinic of Okayama University Hospital. Eligible patients were those who received 3-unit metal-framed 2-retainer (wing–wing) RBFDPs or conventional full-coverage FDPs (RBFDPs/FDPs: 129/177 prostheses). Data were analyzed by Kaplan–Meier analysis with the log-rank test, Mann–Whitney test, chi-square test, and Cox proportional hazards analysis. Results: The 15-year cumulative survival rates were 66.5% for the RBFDP group and 61.6% for the FDP group, which were not significantly different (p = 0.59). The 15-year cumulative event-free rates were 53.4% for the RBFDP group and 59.2% for the FDP group, which were not significantly different (p = 0.52). No significant risk factors related to non-survival and event-free of RBFDPs/FDPs were identified in the analysis model using treatment method, sex, age, number of remaining teeth, and treatment site as explanatory variables. The number of cases in which RBFDPs/FDPs resulted in non-survival due to abutment tooth extraction was significantly lower in RBFDPs (p < 0.01). Further, the abutment tooth as a non-vital tooth was identified as a risk factor for RBFDPs/FDPs resulting in non-survival due to abutment tooth extraction. Conclusions: The present study is the first to indicate RBFDP as a prosthetic treatment option which should be selected for patients with slight or no abutment tooth decay.